You have to trawl for varsity seats - New Straits Times, (2009)
Education is always a hot topic and former journalist Juhaidi Yean Abdullah and medical doctor Noorhaire Nordin, who is doing his PhD, with SONIA RAMACHANDRAN sitting in, have lots to say